Socio-economic and cultural transformation of the Garo community: a qualitative study in Mymensingh District, Bangladesh - Md. Azharul Islam Shakib; Rashed Hossain (CV. Literasi Indonesia, 2026)
The current study aimed to identify the socio-economic and cultural transformations of the Garo community in Mymensingh district. This study employed a qualitative research design with the application of a thematic approach. Data were collected by conducting 10 in-depth interviews and 5 key informant interviews using convenience sampling, and the sample size was determined on the basis of data saturation. Among 15 participants, only 7 interviews were recorded, and others were noted by the interviewer. Afterwards, the data were transcribed into English and analyzed thematically. After analyzing the data, we found two main themes, including socio-economic transformations and cultural transformations, as well as several sub-themes under these main themes. With regard to socio-economic transformation, the findings of the study showed that access to higher education and literacy rates have increased, and men joined diversified jobs such as small businesses, day labor, government sectors, NGO, and so on. On the other hand, women have joined specifically in the nursing sector, beauty parlors, and handicraft sectors. Regarding cultural transformation, the study found that while major festivals like ‘wangala’ were still celebrated, the duration of celebration decreased, as well as Bengali and pop culture influenced the traditional festivals. The findings also disclosed that healthcare facilities have expanded, and traditional treatment methods were replaced by many government and private hospitals. The study highlights the importance of sustainable development policies, education, and economic support to ensure a better life for the Garo people along with protecting their identity.